Analisis Potensi Kelelahan Akut Pada Operator Alat Berat Di Area 1 Tambang Bukit Karang Putih PT. Semen Padang (Persero) Tbk Kota Padang Tahun 2016 - Sesmeri Haryani; Hendra Hendra (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2017)
Fatigue is one of the cause of accidents. The objective of this study is to examine acute fatigue potent ial based on a Occupational Fatigue Exhaustion Recovery (OFER) scale and types of heavy equipment, analyze the relationship between work-related fatigue (duration, workload and shift work), response to non-work-related fatigue (age, nutritional status, commuting time, the number of hours of sleep) with the occurrence of fatigue on heavy equipment operator. This research was conducted from April until July 2016 at heavy equipment operator in the mine area 1 Bukit Karang Putih. Number of study respondents 50 people. The study is observational quantitative research with cross-sectional method. Measurement of fatigue using a OFER scale and the results show that 48% of respondents experiencing moderate acute fatigue, 44% of dump truck experiencing high acute fatigue, shift has significant correlation with high and moderate acute fatigue potential (p value = 0.027). recomendation to company PT Semen Padang to provide education or training about risk factor fatigue to heavy equipment operator.